Thoughtful paths of Nature Park „Ogres Zilie kalni” - Čaupale, Renāte; Kraukle, Ieva; Hofmane, Anete (Landscape Architecture and Art, 2023)
In many countries around the world, urbanization has led to a disconnection from nature within major cities and this has prompted increased research into the significance of nature in the daily lives of urban residents. In the wake of COVID-19 pandemic, people began to visit the walking trails en masse and the habit has continued even after the COVID-19 pandemic. This study, which was conducted in July of 2023 is a part of a broader research initiative aimed at enhancing recreational opportunities and optimizing the physical and wellness benefits provided by walking paths. The research is centered on the "Ogres Zilie kalni" nature park, which features recreational and activity trails. For a majority of residents, these walking paths and ski tracks are vital for recreation. The research’s objective is to outline the planning principles for the nature park’s trail network, drawing not only from landscape architecture but also from the field of environmental psychology. This holistic approach is expected to yield better recreational outcomes and subsequently improve human health. The primary goal of this study is to investigate how different types of nature walking trails impact human attention dynamics. Using Schulte’s Tables, a psychological method, the study assessed how various stimuli in trail planning and route selection influence human attention. The research results do not offer a definitive answer regarding the influence of path type on attention dynamics. However, the findings indicate that attention dynamics tend to improve after the second or third measurement, typically occurring at 20-30 minute intervals. This aligns with the theory that 20 minutes is sufficient for attention reset. Attention dynamics then diminish towards the end of the walk due to physical exhaustion. It was hypothesized that adequate rest could lead to improved dynamics. In the modelling of the walking path network and route selection, cognitive factors such as the purpose of the walk, group participation, individual walks, social interactions, and the perception of the three-dimensional spatial environment serve as the foundation for designing the layout of walking paths. The study raises intriguing and complex research questions, further complicated by the diverse groups involved, including students, families, and the elderly. Social factors play a pivotal role in determining the optimal path for both fundamental research and practical applications. Understanding the mechanisms and information sources guiding decision-making in path selection should encompass not only psychological but also social aspects.